Defisit Tindak Tutur Penderita Skizofrenia di Balikpapan: Kajian Pragmatik Klinis - Yessy Ade Winarti; M. Jafar Haruna; Bibit Suhatmady (Universitas Mulawarman, 2023)
This study aims to examine the form of speech act deficit and conversation structure deficit in the speech of schizophrenia patients at Klinik Ego Balikpapan. This research is qualitative research with a clinical pragmatics approach. The research location is at Klinik Kesehatan Jiwa Ego Balikpapan. This research's data collection technique is free listening (SBLC). The data analysis technique is through data collection, reduction, presentation, analysis, and conclusion. The results of the research on the form of speech act deficit of schizophrenia patients: (1) descriptive locution deficit, (2) assertive illocution deficit, and (3) declarative illocution deficit. The conversational structure deficits found: were (1) conversational turns, (2) adjacent pairs, and (3) pauses. Patients experience pragmatic deficits with a pattern of not being able to speak with a completely clear sentence pronunciation, often repeating sentences, and their speech is slightly slower than normal people in general. However, interlocutors can accept the communication skills of schizophrenic patients because they have good information power. Patients can be invited to talk even though the answer response is chattering according to their wishes as a form of their delusions, and there are some utterances with words with unclear meanings.